Immunological and Clinical Parameters of Newcastle Disease Vaccination in Bronze Turkeys (Meleagris gallopavo) - Schmidt, Elizabeth Moreira dos Santos; Paulillo, Antonio Carlos; Martins, Gislaine Regina Vieira; Denadai, Janine; Lapera, Ivan Moura (International Journal of Poultry Science, 2010)
Clinical and immunological aspects of female Bronze Turkeys, on breeding season, vaccinated against Newcastle disease were evaluated. Seventy-five female Turkeys were distributed into five different experimental groups, vaccinated or not against Newcastle disease: G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain), G4 (LaSota strain inactivated and emulsified in mineral oil) and G5 (not vaccinated-control). The immune response was evaluated by the HI test. Female Turkeys showed high antibody titres when vaccinated against Newcastle disease with live LaSota and inactivated LaSota strains and a moderated to elevated antibody response when vaccinated with Ulster 2C and B1 strains. No clinical signs associated with post-vaccinal reactions were observed.